The effect of awake prone position in non-intubated patients with COVID-19: A feasibility randomized controlled trial - Indawati, Eli; Fauzi, Achmad; Farida, Siti Ida (Jurnal Keperawatan Padjadjaran, 2025)
Introduction: The duration of discomfort and clinical benefits of lying prone in Indonesian clinical settings remain unknown, with the accumulation of prone hours potentially impacting results. The study aimed to test the effect of awake prone position in non-intubated patients with covid-19. Methods: This study used a feasibility randomized control trial. The research was conducted at two general hospitals in Jakarta, Indonesia. This study used a computerized random number generator was used to assign patients to intervention and control groups.  The sample is adult patients who admitted to the hospital with hypoxic respiratory failure due to a positive COVID-19 test. A total of 70 patients were randomly assigned to each group, with 35 individuals being included in the analysis. The intervention involved bed-side nurses encouraging patients to lie prone for at least 6 hours daily, with additional pillows provided for comfort. Significant prone position sessions were recorded if they lasted more than 30 minutes in both arms, lasting for 7 days. Results: The intervention group of patients achieved 65.7% adherence to the intervention protocol. After 2 hours, the P/F ratio was significantly different across the groups, but no significant different between intervention and control group, in term of respiratory escalation, length of stay, or mortality. However, 5.7% of patients in intervention group and 11.4% of patients in control group died due to respiratory failure. Conclusions: Clinical trial conditions have shown that non-intubated patients can be placed in an awake prone position without harm, and this information could be used to help design protocols for future large randomized controlled trials.